GAME EDUKASI WORD SEARCH PUZZLE NAMA ANAK HEWAN DALAM BAHASA SUNDA MENGGUNAKAN ALGORITMA LINEAR CONGRUENT METHOD (LCM) DAN ALGORITMA KNUTH MORRIS PRATT (KMP) (Studi Kasus : SDN Pajawanlor) - Dessi Hermawaty; Rio Andriyat Krisdiawan; Yati Nurhayati (FKOM UNIKU, 2019)
Sundanese has unique names in its daily scope, such as naming animals. Learning the names of animal child using Sundanese is one of the activities in preserving Sundanese culture. However, especially elementary school students have lacked interest in learning Sundanese, one of them concerning the names of animal child in Sundanese, this is because the learning medias are less attractive, there are no developments in the packaging of Sundanese materials, especially the introduction to names of animal child and the absence of a dictionary regarding to the names of children in the school. Therefore, an interesting application is needed to help learning Sundanese so that students have an interest in learning the names of animal child in Sundanese. The result of this study is a game application, in which there are material about the names of animal child in Indonesian and Sundanese and there are questions that must be answered in a certain time limit to practice Sundanese language skills and to know the extent to which students understand Sundanese. By using the Linear Congruent Method (LCM) algorithm to scramble the questions that appear in the game and Knuth Morris Pratt (KMP) for matching strings in the game. The application is built using the C# programming language and the development tools used are Unity. And the system development method in this application uses the Rational Unified Process (RUP) method, while the method for designing the system uses the Unified Modeling Language (UML). Keywords : Sundanese, Linear Congruent Method, Knuth Morris Pratt